2008
DOI: 10.4102/sajr.v12i3.562
|View full text |Cite
|
Sign up to set email alerts
|

Schizencephaly on fetal MRI

Abstract: Schizencephaly is a rare CNS malformation consisting of a full-thickness CSF-filled parenchymal cleft lined by grey matter. Schizencephaly can be diagnosed on prenatal ultrasound but requires magnetic resonance imaging (MRI) for more specific diagnostic differentiation from other cerebrospinal fluid (CSF)-containing structures as well as for detection of associated features.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…There are limited reports of fetal schizencephaly using iuMR imaging—for example, small case series [ 16 ] and case reports [ 17 19 ] with the largest case series to date by Nabavizadeh et al [ 20 ] who reported 10 fetuses with schizencephaly on iuMR imaging and confirmed on post-natal imaging including eight bilateral cases. One interesting finding in that study was a morphological change in the type of cleft between the pre-natal and post-natal imaging as 47% of the ‘open-lip’ schizencephalies detected in utero had become ‘closed lip’ on post-natal imaging.…”
Section: Discussionmentioning
confidence: 99%
“…There are limited reports of fetal schizencephaly using iuMR imaging—for example, small case series [ 16 ] and case reports [ 17 19 ] with the largest case series to date by Nabavizadeh et al [ 20 ] who reported 10 fetuses with schizencephaly on iuMR imaging and confirmed on post-natal imaging including eight bilateral cases. One interesting finding in that study was a morphological change in the type of cleft between the pre-natal and post-natal imaging as 47% of the ‘open-lip’ schizencephalies detected in utero had become ‘closed lip’ on post-natal imaging.…”
Section: Discussionmentioning
confidence: 99%